A note on Linnik’s theorem on quadratic non-residues - Balister, P; Bollobás, B; Lee, J; Morris, R; Riordan, O (Springer International Publishing, 2019)
We present a short and purely combinatorial proof of Linnik’s theorem: for any ε>0 there exists a constant Cε such that for any N, there are at most Cε primes p≤N such that the least positive quadratic non-residue modulo p exceeds Nε .